Gastric emptying and quality of life after pancreatoduodenectomy with retrocolic or antecolic gastroenteric anastomosis. Issue 9 (18th June 2015) - Eshuis, W. J.; de Bree, K.; Sprangers, M. A. G.; Bennink, R. J.; van Gulik, T. M.; Busch, O. R. C.; Gouma, D. J.
<x xml:space="preserve">Abstract</x> Background Delayed gastric emptying (DGE) is a major problem after pancreatoduodenectomy (PD). A recent multicentre randomized trial reported no difference in gastric emptying rates between retrocolic and antecolic reconstruction routes. The present study looked at quality of life with these two approaches and the correlation with gastric emptying. Methods This was a substudy of patients completing a panel of quality‐of‐life questionnaires within a randomized trial comparing retrocolic and antecolic gastroenteric reconstruction after PD. Gastric emptying was assessed by scintigraphy 1 week after surgery. Quality of life was measured with the EuroQoL – 5D questionnaire (EQ‐5D™), the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire (QLQ‐C30) with its pancreatic cancer module (PAN26), and the Gastrointestinal Quality of Life Index (GIQLI). Results There were 38 patients in the retrocolic and 35 in the antecolic group. Baseline characteristics and clinical outcomes were similar in the two groups. Median time to half‐emptying of stomach content after surgery was 145 and 64 min in the retrocolic and antecolic group respectively (P = 0·189). Median percentages of residual activity after 2 h were 64 and 28 per cent respectively (P = 0·213). Quality of life did not differ at any time point between the groups. At 2 weeks after surgery, patients with DGE had significantly worse outcomes on two EQ‐5D™ domains, ten QLQ‐C30/PAN26 subscales, and two GIQLI subscales and total score. Effect sizes were moderate to large. Conclusion The route of gastroenteric reconstruction after PD does not influence either gastric emptying at scintigraphy or quality of life. The impact of DGE on quality of life is clinically significant. Registration number NTR1697 (www.trialregister.nl).